Análise da tensão limite de escoamento em emulsões A/O de petróleo parafínico - Vargas, Gabriel Gomes (2017)
Non-Newtonian fluids formed by dispersions, such as emulsions, solutions and gels,may exhibit viscoelastic, viscoplastic and thixotropic characteristics. When a waxycrude oil is subjected to low temperatures, its paraffin crystals precipitated, giving riseto a resistant structure. The understanding of this behavior at this critical condition isessential to analyze the restart of production in oil wells and pipelines after a produc-tion shutdown. The dimensioning of equipment used in the starting of these systemsdepends fundamentally on the yield stress of the oil in production. The dependence ofthe rheological characteristics of petroleum with the history of shear and temperaturemakes rheological evaluations complex, sometimes imprecise and with low repeatabi-lity. In this work the analyzes were conducted in a commercial type rheometer (HaakeMars III), using plate-plate geometry. Evidence indicates that the initial oil preheatingtemperature is an important variable in the rheological behavior of the fluid. The resultsindicate that the initial increase in temperature causes a severe increase in yield stressup to80◦C, above this temperature there is a dramatic reversal in the yield stress in thetwo oils studied. It is also shown the variation of the yield stress with the change of thecooling rate that the oil is exposed and an analysis of the evaporation and loss of vo-latiles. In the complex study of emulsions, droplet size distribution measurements andmorphological studies were performed. Important considerations are discussed herewith respect to yield stress in low water cut emulsions and high water cut emulsions.Finally, a model is presented for checking the rheological parameters.Keywords: Yield stress, waxy crude oil, Emulsion.